PROGRESSIVE MUSCLE RELAXATION EFFECT ON THE LEVEL ANXIETY of CANCER PATIENTS UNDERGOING CHEMOTHERAPY - enny virda yuniarti; Ima Rahmawati (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2018)
The physical effects of cancer and its therapy can lead to an unpleasant emotional experience. Long-term treatment of chemotherapy and the presence of perceived side effects can cause anxiety. One of the nonpharmacological measures to overcome this anxiety is the relaxation of Progressive Muscle Relaxation therapy. to know the effect of relaxation Progressive Muscle Relaxation on the level of anxiety in cancer patients who underwent chemotherapy. Independent Variables are Progressive Muscle Relaxation and Dependent Variables of Anxiety Level. This research design uses Pre- Experiment with Pretest-Posttest approach design. Sample amounted to 30 people. Sampling technique Purposive Sampling. The tool used in the HRS-A (Hamilton Rating Scale-Anxiety) questionnaire. The research was conducted from March to April 2017 at Leprosy Hospital SumberGlagahPacet, Mojokerto. Progressive Muscle Relaxation performed one up to two times for 3 weeks with a duration of 15 minutes per session. The test statistic used is to use the Wilcoxon Rank Test test. Ï = 0.046 and Î± = 0.05 so that means H0 rejected and H1 accepted which means there is influence progressive muscle relaxation to the level anxiety cancer patients who underwent chemotherapy at Leprosy Hospital Pacet, Mojokerto. Progressive Muscle Relaxation is recommended as one of the non-pharmacological complementary therapies because this relaxation technique is easy to do and does not cost.